Громадянське виховання як спеціальний напрям позашкільної освіти - Єгорова, Олександра; Yehorova, O. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлюються теоретичні аспекти і значення громадянського виховання у його вузькому значенні на сучасному етапі та аналізується передовий досвід та успішні практики позашкільної освіти у США у галузі громадянської освіти і виховання. Обгрунтовується громадянське виховання у позашкільній освіті США як системний об‟єкт у змістовому і процесуальному його аспектах, що має на меті формування національних, загальнолюдських цінностей, громадянcької активності та компетентностей, необхідних особистості у XXI столітті. Встановлено, що громадянське виховання є одним з пріоритетним напрямків шкільної і позашкільної освіти у США і є перспективним напрямком для позашкільної освіти України. The article covers the theoretical aspects and importance of civic education in its narrow sense at the present stage and analyzes the best experiences and successful practices of afterschool education in the United States in the field of civic education and upbringing. It also reveals about the broad consideration of civic education in the USA, civic education in afterschool education of the United States is substantiated as a systematic object in its substantive and procedural aspects, which aims to form national, universal human values, civic activity and competencies required for the personality to obtain in the XXI century. It is found out that these skills are : the integration of knowledge, skills and values, critical thinking, the skills of achieving compromise and mutual respect, solving social problems involving different sides, orientation in political systems and processes. It has been established that the civic education is one of the priority areas of school and out-of-school education in the United States and is a promising area for afterschool education in Ukraine.
Civic education as a special direction of afterschool education
Keywords: позашкільна освіта; громадянська освіта; громадянське виховання; компетентності XXI століття; навчання громадянськості; патріотичне виховання; залучення у демократію; afterschool (out-of-school) education; civic education; civic upbringing; the XXI century competences; teaching citizenship; patriotic education; involvement in democracy